Stroke profile and outcome between urban and rural regions of Northwest India: Data from Ludhiana population-based stroke registry. (December 2017) - Kaur, Paramdeep; Verma, Shweta J; Singh, Gagandeep; Bansal, Rajinder; Paul, Birinder S; Singla, Monika; Singh, Shavinder; Samuel, Clarence J; Sharma, Meenakshi; Pandian, Jeyaraj D
Introduction: The objective of this study is to compare the clinical profile, risk factors, type and outcome of stroke patients in urban and rural areas of Punjab, India. Methods: The primary data source was from the Ludhiana urban population-based stroke registry. The data of first-ever stroke patients with age ≥18 years were collected using WHO stepwise approach from all hospitals, general practitioners, physiotherapy and scan centres between 26 March 2011 and 25 March 2013. Results: A total of 4989 patients were included and out of 4989 patients, 3469 (69%) were from urban areas. Haemorrhagic stroke was seen more in rural as compared to urban regions (urban 1104 (32%) versus rural 552 (36%); p = 0.01). There were significant differences seen in stroke risk factors; hypertension (urban 1923 (84%) versus rural 926 (89%); p = 0.001) and hyperlipidaemia (urban 397 (18%) versus rural 234 (23%); p = 0.001) between two groups. In the multivariable analysis the rural patients were more likely to be younger (age < 40 years) (OR: 1.82; 95% CI: 1.24–2.68; p = 0.002), Sikhs (OR: 2.57; 95% CI: 1.26–5.22; p = 0.009), farmers (OR: 9.41; 95% CI: 5.36–16.50; p < 0.001), housewives (OR: 2.71; 95% CI: 1.45–5.06; p = 0.002), and consumed alcohol (OR: 1.57; 95% CI: 1.19–2.06; p = 0.001) as compared to urban patients. In addition, use of imaging was higher in rural patients (OR: 1.99; 95% CI: 1.06–3.74; p = 0.03) as compared to urban patients. Discussion and Conclusion: In this large cohort of patients, rural and urban differences were seen in risk factors and type of stroke. Stroke prevention strategies need to take into consideration these factors including regional sociocultural practices.